The Influence of Family Function on State Anxiety of Chinese College Students During the Epidemic of COVID-19 - Yang, Lingping; Wu, Miao; Wang, Yuqi; Peng, Bin (Frontiers in Psychology, 2021)
The Coronavirus Disease 2019 (COVID-19) may affect mental health. There’s few research about the influence of family function on state anxiety of college students in the context of global pandemic. The aim of the study was to clarify that generalized anxiety disorder (GAD) and trait anxiety had mediating effects in family function on state anxiety of Chinese college students following the "stay-at-home" order during the outbreak of COVID-19. This cross-sectional study was conducted online with 1039 respondents (median age 22, 344 were males and 695 were females). We analyzed demographics, The State-Trait Anxiety Inventory (ST-AI) and Chinese Family Function Scale (FAD-18), Generalized Anxiety Disorder-7 (GAD-7) and used path analysis to discuss the influence of family function on state and trait anxiety. The total score of S-AI was (36.84±10.26) for men and (38.36±8.91) for women, and that of T-AI was (38.04±9.86) for men and (39.45±8.90) for women. The results showed that the state and trait anxiety of female students were higher than that of male students (P < 0.05). The state and trait anxiety of medical students were lower than that of literature students (P < 0.05). The GAD of male was lower compared with female. The score of family function has significant differences in gender, age, education and region(P < 0.05). State anxiety was posotively correlated with family function, trait anxiety and GAD (r=0.25~0.85, P <0.001). GAD and trait anxiety had a complete meditating effect between family function and state anxiety (the proportion of standard indirect mediating effect was 28.28%). Family funtion needs be much accounted of society during the COVID.